2016
DOI: 10.1016/j.mad.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Development of the adaptive NK cell response to human cytomegalovirus in the context of aging

Abstract: Human cytomegalovirus (HCMV) establishes a highly prevalent life-long latent infection. Though generally subclinical, HCMV infection may have severe consequences during fetal development and in immunocompromised individuals. Based on epidemiological studies HCMV(+) serology has been associated with the development of atherosclerosis, immune senescence and an increase mortality rate in elderly people. Such long-term detrimental effects of the viral infection presumably result from an inefficient immune control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Our results show that CMV seropositivity in young individuals associates with a significant increase in the percentage of CD56 dim NK cells expressing Eomes and a decreased percentage of T-bet hi NK cells within the CD56 dim CD57 + subset, suggesting that changes in the expression of these transcription factors are involved in CMV-induced remodeling of NK cells, characterized by the expansion of CD56 dim CD57 + NK cells coexpressing NKG2C activating receptors (2, 14, 30, 60, 79). It has been reported that the level of expression of Eomes and T-bet is strongly reduced in NK cells from allogeneic hematopoietic stem cell transplantation recipients compared with healthy control subjects and that acute graft-versus-host disease and CMV reactivation are associated with further downregulation of T-bet (80) supporting the importance of these transcription factors in the generation and differentiation of NK cells and in the response against CMV after hematopoietic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our results show that CMV seropositivity in young individuals associates with a significant increase in the percentage of CD56 dim NK cells expressing Eomes and a decreased percentage of T-bet hi NK cells within the CD56 dim CD57 + subset, suggesting that changes in the expression of these transcription factors are involved in CMV-induced remodeling of NK cells, characterized by the expansion of CD56 dim CD57 + NK cells coexpressing NKG2C activating receptors (2, 14, 30, 60, 79). It has been reported that the level of expression of Eomes and T-bet is strongly reduced in NK cells from allogeneic hematopoietic stem cell transplantation recipients compared with healthy control subjects and that acute graft-versus-host disease and CMV reactivation are associated with further downregulation of T-bet (80) supporting the importance of these transcription factors in the generation and differentiation of NK cells and in the response against CMV after hematopoietic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 72%
“…These cells have some characteristics of adaptive immunity and are considered “memory” or “adaptive” NK cells (5558). The magnitude of the expansion of NKG2C high NK cells is determined by the magnitude of the proinflammatory cytokine secretion upon NK cell activation (59), and it has been proposed that these cells contribute to the proinflammatory environment based on the relation between the percentage of NKG2C + cells, elevated levels of PCR, and cardiovascular risk determinants of CMV-seropositive individuals (60, 61). …”
Section: Discussionmentioning
confidence: 99%
“…between the levels of % NKG2C + cells and the risk for posttransplant CMV viremia was independent of age. Actually, there is no evidence supporting a relation between aging and the development of adaptive NKG2C + cells in CMV + individuals (32). Despite the limited in vitro direct response of adaptive NK cells against CMV-infected cells, presumably under the influence of viral immune evasion mechanisms, they have been shown to efficiently mediate virus-specific Ab-dependent cytotoxicity and cytokine production triggered through the FcgRIIIa (CD16) receptor (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Expansions of NKG2C + cells following HCMV infection were reported in immunosuppressed transplant recipients ( 65 , 66 , 74 ), in a severe T cell primary immunodeficiency ( 75 ), as well as in children and newborns with congenital or postnatal HCMV infection ( 76 , 77 ), independently of aging ( 78 80 ). Altogether, these observations suggest that the magnitude of the HCMV imprint on the NK cell compartment in healthy individuals is likely fixed at the time of primary infection, presumably depending on host/virus genetics and other circumstantial factors (e.g., age at infection, viral load, etc.)…”
Section: Nk Cells and Hcmv Infection In Ktrmentioning
confidence: 99%
“…The frequencies of TcRαβ T cells specific for HCMV antigens (e.g., IE-1 and pp65) have been reported to predict the risk of posttransplant infection ( 109 , 110 ); moreover, TcRγδ T cells were associated with control of posttransplant HCMV viremia ( 111 ). Adaptive NKG2C + NK cells and CTL have been proposed to be independent ( 78 80 ). Thus the possibility that the association of adaptive NKG2C + NK cells with a lower risk of HCMV infection might indirectly reflect a central role of HCMV-specific TcRαβ T cells (Figure 3 ) appears unlikely; further studies are warranted to precisely address this issue.…”
Section: Nk Cells and Hcmv Infection In Ktrmentioning
confidence: 99%